ANALYSIS OF MESOSCALE CONVECTIVE COMPLEX DURING MJO PERIOD IN INDONESIA (Case Study : Moluccas) - Maharani Savitri, Jenita
The large sea area in Indonesia caused many evaporation occur in Maritime Continent. This evaporation influence the convective activity, which rapidly form storm clouds. One of them is called as Mesoscale Convective Complex (MCC). MCC identified by Grab ‘em Tag ‘em Graph ‘em (GTG) algorithm using Tempearature Black Body (TBB) IR 1 data from GPM_MERGRIR during 5 year from 2010 until 2014. Besides knowing the characteristic of MCC in Moluccas, also analyzed the influence of Madden Julian Oscillation (MJO) to MCC that occur especially in Moluccas. The result found that characteristics of MCC in Moluccas have greater average duration 13.1 hours compared with Indonesia with 11.3 hours duration. Mature time MCC in Moluccas in range at 03.00-05.00 LT and 15.00-17.00 LT. While, in Indonesia at 06.00-08.00 LT. If it analyzed per hours, frequency of MCC in Moluccas most occur at 06.00-19.00 LT, and in Indonesia at 10.00 LT. However, Moluccas and Indonesia show semi diurnal characteristic. Besides that, initial time and dissipation time both same at 01.00 and 00.00 LT. Then both most occur when MAM, with JJA is also the most occur month of MCC in Moluccas. In case of MCC when MJO produce more MCC. But, another case show that when non MJO event, also produce high frequency of MCC. In phase 3, phase 4, and phase 5 of MJO, MCC doesn’t seem propagate. While for propagation of integrated column MSE anomaly eastward more visible when MJO event than non MJO event. But, also propagation of integrated column MSE anomaly is not significant. Thus, the impact of MJO is not very apparent on the MCC event both in the increasing number and the propagation of MCC.